Eﬀect of phospho-compost and phosphate laundered sludge combined or not with endomycorrhizal inoculum on the growth and yield of tomato plants under greenhouse conditions - EL Gabardi, Soumaya; Mouden, Najoua; Chliyeh, Mohamed; Selmaoui, Karima; Ouazzani Touhami, Amina; Filali-Maltouf, Abdelkarim; Ibnsouda Koraichi, Saad; Amir, Soumia; Benkirane, Rachid; EL Modafar, Cherkaoui; Douira, Allal (Acta Biologica Szegediensis, 2021)
The study aims to evaluate the eﬀect of endomycorrhizal inoculum (arbuscular mycorrhizal fungi), phospho-compost and phosphate sludge in single (M, PC, PS) or dual combinations (PC+M, PS+M, PS+PC) compared to agricultural and Mamora soils (A and S) on the growth, ﬂowering, and yield of tomato plants. Among the studied treatments, the substrates containing 5% of phospho-compost combined with endomycorrhizal inoculum (PC+M) gave the most positive eﬀect followed by phospho-compost (PC) and endomycorrhizal inoculum (M). In response to PC+M substrate, tomato plant height, the number of leaves and ﬂowers attained 90 cm, 30, and 25, respectively. In substrates PC and M, tomato plants showed a height of 85 and 75 cm, leaves number of 30 and 19 leave/plant and number of ﬂowers of 21, and 19 ﬂower/plant. An optimal yield with (12 fruits/plant) was recorded in tomato plants grown on the substrate amended with bio-inoculant (AMF) and phospho-compost at a rate of 5%. In terms of qualitative parameters, the highest fresh and dry weight of aerial plant parts and root system were recorded in tomato plants grown in culture substrate incorporating 10 g of endomycorrhizal inoculum and 5% of phospho-compost reaching respectively103.4 g, 34 g 90.1 g, 28.9 g as compared to 87, 51, 23 and 24.1 g noted by tomato plants on the substrate with phospho-compost (5%) (PC). The highest mycorrhization parameters (frequency (F), intensity of mycorrhization (M), average arbuscular content (A), average vesicular content (V), average intraradicular spore content (S)) were found in the roots of tomato plants growing on substrates amended with 5% phospho-compost plus 10 g of endomycorrhizal inoculum, with percentages of 100% F, 61% M, 40.67% A, 18.36% V, and 56.9% S.